2010
DOI: 10.1108/17538271011080637
|View full text |Cite
|
Sign up to set email alerts
|

Residential market development in sub‐Saharan Africa

Abstract: Purpose -There is a general consensus that residential submarkets exist, but the basis upon which these are specified remains the subject of debate. The purpose of this paper is to model data on different residential locations in Ghana to show how the submarkets have performed over the past 16 years. Design/methodology/approach -The paper employs hedonic modelling based on 3,250 sale transactions and 1,130 rental transactions from 1992 to 2007. Findings -The results demonstrate that five residential real estat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Previous studies suggested submarket existence based on several market segmentations (Schnare & Struyk 1976;Goodman 1978;Allen et al 1995;Fletcher et al 2000;Goodman & Thibodeau 2007;Anim-Odame et al 2010a;Anim-Odame et al 2010b;Wu & Sharma 2012;Wheeler et al 2014). The results suggest that submarkets exist for a structural segmentation of the market than for a full span of spatial segmentation.…”
Section: _______________________________________________________ 259mentioning
confidence: 72%
See 3 more Smart Citations
“…Previous studies suggested submarket existence based on several market segmentations (Schnare & Struyk 1976;Goodman 1978;Allen et al 1995;Fletcher et al 2000;Goodman & Thibodeau 2007;Anim-Odame et al 2010a;Anim-Odame et al 2010b;Wu & Sharma 2012;Wheeler et al 2014). The results suggest that submarkets exist for a structural segmentation of the market than for a full span of spatial segmentation.…”
Section: _______________________________________________________ 259mentioning
confidence: 72%
“…The 18 th AFRES ANNUAL CONFERENCE 2018 analysis and this is very useful in appreciating market dynamics and making market predictions (Wheeler et al 2014). Housing markets research continues to receive little attention from researchers and research in this area is characterised by data unavailability and asymmetries (Anim-Odame et al 2010a;Anim-Odame et al 2010b).…”
Section: _______________________________________________________ 236mentioning
confidence: 99%
See 2 more Smart Citations
“…In Nigeria (Arimah, 1992;Adegoke, 2014), Kenya (Gulyani & Talukdar, 2008), Togo (Choumert, Kere, & Laré, 2015) and Uganda (Knight, Herrin, & Balihuta, 2004), the extant literature has focused on the effects of specific location and neighbourhood attributes on rental value. In Ghana, for example, studies such as Anim-Odame et al (2010a), Anim-Odame et al (2010b), Owusu-Ansah (2012a), Owusu-Ansah and Abdulai (2014), Owusu-Ansah et al (2017), have relied on data from land sector agencies and valuation reports to examine the dynamics of the property markets in Kumasi, Accra and Tema. These studies, however, were limited to residential property values and price dynamics.…”
Section: Introductionmentioning
confidence: 99%